Emerging research on networked multimedia communication systems - Kanellopoulos, Dimitris N. (Advances in multimedia and interactive technologies book series, 2016)
This book provides a comprehensive overview of the most current theoretical frameworks, technological developments, and empirical research findings in the field of electronic media.